Teachers’ Strategies in Teaching Reading at Junior High Schools in Sirimau Sub-District - Gladiora N. Tuhumury; Renata C. G. V. Nikijuluw (MATAI: International Journal of Language Education, 2020)
The purpose of this research is to explain the understanding of teachers about the method of teaching reading comprehension, the techniques that are widely used, the challenges encountered by the teacher and the approaches that have been found to solve these problems. This used the template of the survey using a hybrid approach, where the results were gathered in quantitative and qualitative terms. The subjects of this research were 35 junior high school English teachers in Ambon city. The data collection method was questionnaire, survey and assessment checklist. The findings revealed that the technique plays a significant role in English reading practices; the techniques enable teachers to conduct their teaching tasks faster and well-arranged. Mostly, students use speaking aloud, summarization, vocabulary development, skimming, and testing. In the end, the teachers themselves and the students were faced with the challenges of using the technique in the teaching and learning process. The approaches used by teachers to solve the challenges were enhancing students' knowledge of vocabulary, inspiring pupils, and introducing different methods for teaching literacy. Teachers need to expand their understanding of techniques in the teaching and learning process.